Complete genome analysis of sugarcane root associated endophytic diazotroph Pseudomonas aeruginosa DJ06 revealing versatile molecular mechanism involved in sugarcane development - Guo, Dao-Jun; Singh, Pratiksha; Yang, Bin; Singh, Rajesh Kumar; Verma, Krishan K.; Sharma, Anjney; Khan, Qaisar; Qin, Ying; Chen, Ting-Su; Song, Xiu-Peng; Zhang, Bao-Qing; Li, Dong-Ping; et al. (Frontiers in Microbiology, 2023)
Sugarcane is an important sugar and bioenergy source and a significant component of the economy in various countries in the arid and semiarid. It requires more synthetic fertilizers and fungicides during growth and development. However, excess use of synthetic fertilizers and fungicides causes environmental pollution and affects cane quality and productivity. Plant growth-promoting bacteria (PGPB) indirectly or directly promote plant growth in various ways. In this study, 22 PGPB strains were isolated from the roots of the sugarcane variety GT42. After screening of plant growth-promoting (PGP) traits, it was found that the strain DJ06 had the most potent PGP activity, which was identified as Pseudomonas aeruginosa by 16S rRNA gene sequence. Scanning electron microscopy (SEM) and green fluorescent protein (GFP) labeling technology confirmed that the DJ06 strain successfully colonized in sugarcane tissues. The complete genome sequencing of the DJ06 strain was performed using Nanopore and Illumina sequencing platforms. The results showed that the strain DJ06 genome size was 64,90,034 bp with a G+C content of 66.34%, including 5912 protein-coding genes (CDSs) and 12 rRNA genes. A series of genes related to plant growth promotion was observed, such as nitrogen fixation, ammonia assimilation, siderophore, 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, indole-3-acetic acid (IAA) production, auxin biosynthesis, phosphate metabolism, hydrolase, biocontrol, and tolerance to abiotic stresses. Additionally, the effect of DJ06 strain was also evaluated by inoculation in two sugarcane varieties GT11 and B8. The length of plant was increased significantly by 32.43 and 12.66% and fresh weight 89.87 and 135.71% in sugarcane GT11 and B8 at 60 days after inoculation. The photosynthetic leaf gas exchange also increased significantly compared with the control plants. The content of indole-3-acetic acid (IAA) enhanced and gibberellins (GA) and abscisic acid (ABA) reduced in response to inoculation of DJ06 strain as compare to control in two sugarcane varieties. The enzymatic activities of oxidative, nitrogen metabolism and hydrolases were also changed dramatically in both sugarcane varieties with inoculation of DJ06 strain. These findings provide better insights into the interactive action mechanisms of P. aeruginosa DJ06 strain and sugarcane plant development.